Going beyond carbon: An "Earth System Impact" score to better capture corporate and investment impacts on the Earth system - Crona, Beatrice; Parlato, Giorgio; Lade, Steven; Fetzer, Ingo; Maus, Victor (Stockholm University, 2023)
This dataset is associated with a paper that uses the mining sector as a case to illustrate how the Earth System Impact (ESI) score could be used to assess impacts of economic sectors, and how this, in turn, could i) represent a scientific basis for improving prioritization of mitigative action within companies, ii) provide support for decisions on where to direct public and private investments. This dataset includes data on environmental pressures, location, revenues, and primary commodity production for assets from a sample of 10 mining companies and showcases how the ESI score could be calculated and interpreted.

This dataset is associated with a paper that uses the mining sector as a case to illustrate how the Earth System Impact (ESI) score could be used to assess impacts of economic sectors, and how this, in turn, could i) represent a scientific basis for improving prioritization of mitigative action within companies, ii) provide support for decisions on where to direct public and private investments. This dataset includes data on environmental pressures, location, revenues, and primary commodity production for assets from a sample of 10 mining companies and showcases how the ESI score could be calculated and interpreted.

Microsoft® Excel® for Microsoft 365 MSO, Version 2304 Build 16.0.16327.20200
Keywords: Business and Management; Earth and Environmental Sciences; Earth System Impact; sustainable investments; environmental impact metrics; corporate environmental impact; mining; environmental performance; planetary boundaries interactions; capital allocation decisions; Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap